Bridging the gap: functional healing of embryonic small intestine ex vivo. (3rd August 2015) - Coletta, Riccardo; Roberts, Neil A.; Oltrabella, Francesca; Khalil, Basem A.; Morabito, Antonino; Woolf, Adrian S.
Abstract: The ability to grow embryonic organs ex vivo provides an opportunity to follow their differentiation in a controlled environment, with resulting insights into normal development. Additionally, similar strategies can be used to assess effects on organogenesis of physical and chemical manipulations. This study aimed to create an organ culture model with which to test physical manipulations to enhance healing of gut segments, thus generating a single functional organ. Embryonic mouse jejunum was isolated and cut into 2–3 mm tubes, which were placed in pairs, separated by a small gap, on semi‐permeable supports. Each pair was linked by a nylon suture threaded through their lumens. After 3 days in organ culture fed by defined serum‐free media, the rudiments differentiated to form tubes of smooth muscle surrounding a core of rudimentary villi. Of 34 such pairs, 74% had touching and well aligned proximate ends. Of these joined structures, 80% (59% of the total pairs) had a continuous lumen, as assessed by observing the trajectories of fluorescent dextrans injected into their distal ends. Fused organ pairs formed a single functional unit, as assessed by spontaneous contraction waves propagated along their lengths. In these healed intestines, peripherin + neurons formed a nexus in the zone of fusion, linking the rudiment pairs. In future, this system could be used to test whether growth factors enhance fusion. Such results should in turn inform the design of novel treatments for short bowel syndrome, a potentially fatal condition with a currently limited and imperfect range of therapies. ©2015. The Authors Journal of Tissue Engineering and Regenerative Medicine Published by John Wiley & Sons, Ltd